The oyster revolution: shell middens, shell temper, and settling down in North America’s Chesapeake region - Jenkins, Jessica A.; Gallivan, Martin D. (Frontiers in Human Dynamics, 2024)
Transformative social change occurred in the Chesapeake region with the intensification of oyster harvesting and the establishment of central places in estuarine settings at the outset of the Middle Woodland period (ca. A.D. 200). Accompanying the pivot toward estuarine living was the spread of shell-tempered ceramics indexing regional social networks from the Delaware Bay to the mouth of the Chesapeake Bay. Survey and excavation data from the Naval Weapons Station Yorktown (NWSY) on the York River trace this process on Virginia’s lower York River. Here, Middle Woodland populations established central places around the lower embayed portions of tidal creeks. Communal shell middens anchoring these central places offer evidence of intensive oyster harvesting and a history of periodic overharvesting, adjustment, and long-term sustainability. We hypothesize that common pool resource management, i.e. collective action and stewardship in the management of the oyster fishery, was an important part of Native societies’ settling down in this region.